2019
DOI: 10.1101/630996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA-sequencing of differentiating iPS cells reveals dynamic genetic effects on gene expression

Abstract: 28Recent developments in stem cell biology have enabled the study of cell fate decisions in early 29 human development that are impossible to study in vivo. However, understanding how 30 development varies across individuals and, in particular, the influence of common genetic 31 variants during this process has not been characterised. Here, we exploit human iPS cell lines 32 from 125 donors, a pooled experimental design, and single-cell RNA-sequencing to study 33 population variation of endoderm differentiatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
134
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(139 citation statements)
references
References 65 publications
5
134
0
Order By: Relevance
“…Perturb-seq (Dixit et al, 2016) and ECCITE-seq (Mimitou et al, 2019)) and pooled eQTL screens (e.g. crisprQTL mapping (Gasperini et al, 2019) and Census-seq (Cuomo et al, 2020;Jerber et al, 2020;Mitchell et al, 2020;Neavin et al, 2020)) approaches will more rapidly identify host variants that impact the entry, replication and egress of SARS-CoV-2, cellular survival, and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Perturb-seq (Dixit et al, 2016) and ECCITE-seq (Mimitou et al, 2019)) and pooled eQTL screens (e.g. crisprQTL mapping (Gasperini et al, 2019) and Census-seq (Cuomo et al, 2020;Jerber et al, 2020;Mitchell et al, 2020;Neavin et al, 2020)) approaches will more rapidly identify host variants that impact the entry, replication and egress of SARS-CoV-2, cellular survival, and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion Single-cell RNA-seq eQTL analyses define an emerging research niche that brings major benefits for the understanding of functional genetic variation including the identification of cell-type and condition-specific correlations (2,(13)(14)(15)(16)45). In this paper, we present a new eQTL-based analysis in a scRNA-seq setting -scReQTL -which uses the VAFRNA at expressed heterozygous SNVs in place of the genotypes, to correlate allele prevalence to geneexpression levels.…”
Section: Functional Screqtls Snvs Annotationsmentioning
confidence: 99%
“…By utilizing the advantages of the single cell resolution, these studies have revealed many new regulatory SNVs, including those with cell-specific or transient effects (2)(3)(4)(13)(14)(15)(16). To assess GE, these methods employ approaches specific to single cell transcriptomics, including accounting for drop-outs, classification of cells by type, and assessments of progressive cell stages (2)(3)(4)(13)(14)(15)(16). SNV information is traditionally obtained from the genotypes across multiple individuals and encoded as the number of alleles (0, 1 or 2) bearing the variant nucleotide.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified cell type specific eQTL using scRNA-seq which were unobservable in bulk RNA-sequence studies 25–29 . The first study to report this enhanced cell type specific eQTL detection from scRNA-seq investigated 92 genes measured in 1,440 single cells from lymphoblastoid cell lines in 15 individuals 27 .…”
Section: Introductionmentioning
confidence: 99%